Analysis Of Student Interest In Science Teaching At Grade 5 Of Muhammadiyah 25 Elementary School, Medan Tembung District, North Sumatra - Sulasti, Berbi; Pratiwi, Indah; Tarigan, Muna Azizah Zahra (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The Meaning of Science Lessons as one of the lessons tested nationally needs to be improved in the quality of the lessons. The government has made many efforts to improve the quality of national education, including science education. Science education at the elementary school level will be able to make a significant contribution to the whole process of children's education at the next level and enrich their knowledge about nature and its phenomena. This study aims to determine students' interest in learning science in elementary schools. The research method used is a qualitative method. This research was conducted on May 17 2023. The subjects of this research were fifth grade students at SD Muhammadiyah 25, Jl. Pukat l N.19, Bantan Tim., Medan Tembung District, Medan City, North Sumatra. The data collection technique used is by giving questionnaires to students to fill out.Keywords: interest, study, science, elementary school